New polychaete species collected during the expeditions ANDEEP I, II, and III to the deep Atlantic sector of the Southern Ocean in the austral summers 2002 and 2005 - Ampharetidae, Opheliidae, and Scalibregmatidae - Schüller, Myriam (Zootaxa, 2008)
Seven new species of polychaetes are presented from the Southern Ocean deep sea. The ampharetid species Anobothrus pseudoampharete sp. nov. is the third species of its genus reported for the Southern Ocean, the same applies to the scalibregmatid species Pseudoscalibregma papilia sp. nov. Five new opheliid species are described — two belong to the genus Ophelina Örsted, 1843, namely O. ammotrypanella sp. nov. and O. robusta sp. nov. The remaining three species, Ammotrypanella cirrosa sp. nov., A. mcintoshi sp. nov., and A. princessa sp. nov., belong to the formerly monospecific genus Ammotrypanella McIntosh, 1879. Based on these new findings the genus is revised, its type species A. arctica McIntosh, 1879 is redescribed.